HUBUNGAN KEPEMILIKAN BUKU KIA TERHADAP PENINGKATAN PEMANFAATAN PELAYANAN KESEHATAN MATERNAL DI INDONESIA - Suparmi Suparmi; Anissa Rizkianti; Iram Barida Maisya; Ika Saptarini (Jurnal Kesehatan Reproduksi, 2018)
Background: One effort to reduce maternal mortality (MMR) is to increase the use of maternal and child health books (MCH books) as a source of information and maternal health record. However, there are still limited research findings related to the ownership of MCH books. Objective: This study aimed to measure the relationship of MCH book ownership to the increased utilization of maternal health services in Indonesia. Method: Secondary data analysis of the 2016 National Health Indicator Survey (Sirkesnas) was used with a cross-sectional design. The population is all women 10-54 years who gave birth to the last child in the last three years. The number of samples was 7149 respondents. The dependent variable includes antenatal visits, delivery assisted by health professionals and delivery in a health facility. The independent variable is the ownership of the MCH book and the characteristics of the mother (age, occupation, education and residence). Multivariate analysis used multiple logistic regression with 95 percent confidence interval. Results: More than half (57.5%) of mothers have MCH books. After being controlled by maternal characteristics (age, education, place of residence and occupation), MCH book ownership is related to the use of antenatal care services (OR = 2.31, 95% CI: 0,000), delivery by health professionals (OR = 4.49, 95% CI: 0,000), and delivery in a health facility (OR = 2.71, 95% CI: 0,000). Conclusion: The ownership of the MCH handbook is related to the increased utilization of antenatal (K4) services, delivery assisted by health professionals and delivery in a health facility. Latar belakang: Salah satu upaya menurunkan angka kematian ibu (AKI) adalah meningkatkan pemanfaatan buku kesehatan ibu dan anak (buku KIA) sebagai sumber informasi dan pencatatan kesehatan ibu. Namun, masih terbatas hasil penelitian yang berhubungan dengan kepemilikan buku KIA. Tujuan: Studi ini bertujuan mengukur hubungan kepemilikan buku KIA terhadap peningkatan pemanfaatan pelayanan kesehatan maternal di Indonesia. Metode: Analisis data sekunder Survei Indikator Kesehatan Nasional (Sirkesnas) 2016 digunakan dengan desain potong lintang. Populasi adalah semua wanita 10-54 tahun yang melahirkan anak terakhir dalam kurun waktu tiga tahun terakhir. Jumlah sampel adalah 7149 responden. Variabel dependen meliputi kunjungan antenatal, persalinan ditolong oleh tenaga kesehatan dan persalinan di fasilitas kesehatan. Variabel independen adalah kepemilikan buku KIA dan karakteristik ibu (umur, pekerjaan, pendidikan dan tempat tinggal). Analisis multivariat menggunakan regresi logistik ganda dengan derajat kepercayaan 95 persen. Hasil: Lebih dari separuh (57,5%) ibu memiliki buku KIA. Setelah dikontrol oleh karakteristik ibu (umur, pendidikan, tempat tinggal dan pekerjaan), kepemilikan buku KIA berhubungan dengan pemanfaatan pelayanan pemeriksaan kehamilan (OR = 2,31, 95% CI: 0,000), persalinan oleh tenaga kesehatan (OR = 4,49, 95% CI: 0,000), dan persalinan di fasilitas kesehatan (OR = 2,71, 95% CI: 0,000). Kesimpulan: Kepemilikan buku KIA berhubungan dengan peningkatan pemanfaatan layanan antenatal (K4), persalinan ditolong oleh tenaga kesehatan dan persalinan di fasilitas kesehatan.